2011
DOI: 10.1258/jms.2011.011023
|View full text |Cite
|
Sign up to set email alerts
|

Universal Antenatal Screening for Group B Streptococcus in Emilia-romagna

Abstract: Background Group B streptococcus (GBS) is a leading cause of severe infections in newborns. Intrapartum antibiotic chemoprophylaxis (IAP) reduces the rate of early-onset disease. The aim of this study is to determine the degree of clinicians' compliance with the suggested protocol for GBS prevention in Emilia-Romagna (Italy). Methods Characteristics of each delivery were prospectively recorded in the period between October 2005 to December 2005. Standardized pro-forma were used to collect data. Results Among 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
5
17
3
Order By: Relevance
“…The percentage of GBS screened women was higher than the 85% reported from other national and international studies [12,15], and this increase in the adoption of screening has been probably coupled with the use of other recommended prenatal screening tests and with the greater prenatal care utilization [9]. GBS colonization was 9.8% in our population; which is lower than that reported in many previous studies in the literature [9,11,12,16,17], although it is well known that GBS maternal colonization varies from place to place. Moreover, other factors may have contributed to this variation, including socio-economic factors, variable clinical practices, methods in sample collection and processing techniques, as well as ethnic and genetic factors that may play a role in rates of GBS infection [18].…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The percentage of GBS screened women was higher than the 85% reported from other national and international studies [12,15], and this increase in the adoption of screening has been probably coupled with the use of other recommended prenatal screening tests and with the greater prenatal care utilization [9]. GBS colonization was 9.8% in our population; which is lower than that reported in many previous studies in the literature [9,11,12,16,17], although it is well known that GBS maternal colonization varies from place to place. Moreover, other factors may have contributed to this variation, including socio-economic factors, variable clinical practices, methods in sample collection and processing techniques, as well as ethnic and genetic factors that may play a role in rates of GBS infection [18].…”
Section: Discussioncontrasting
confidence: 62%
“…Among women with an indication for GBS prophylaxis, Goins et al [9] and De Luca et al [11] reported optimal IAP in 61.2% and 50% of deliveries, respectively. Berardi et al [12] in a prospective cohort study showed that adequate IAP was administered in 52% of GBS culture-positive women and in 62.2% of the women with unknown GBS status and risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this time, the screen rates increased to 66% and 70% in 2012 and 2013, respectively. The screen rate was still below the surveillance rate (85%) in the USA during 2003–2004, and the 86.6% reported in Italy in 2005 . The isolation rate of GBS from pregnant women was 18–22%, compatible with a previous report from Taiwan …”
Section: Discussionsupporting
confidence: 81%
“…Screening for women requiring IAP has been done using one of two approaches: culture-based universal screening which should be done between weeks 35 and 37 of pregnancy and risk-based approach in which women receive IAP based on the presence of risk factors [1, 4]. Universal Screening policy is practiced in the United States and Canada [1–3, 5] and it is also recommended with some modifications in many European countries and in Japan [6], (http://www.groupbstrepinternational.org/what-is-group-b-strep/early-onset-gbs-disease/), [2]. A risk-based approach is recommended in Denmark, Israel, the Netherlands, New Zealand and the United Kingdom [1, 2].…”
Section: Introductionmentioning
confidence: 99%